Performance analysis: an essential tool for the early detection’s risks of failure in the company - HAFID , Fethi; DANI EL KEBIR, Nacera (Journal of Research in Finance and Accounting, 2026)
The financial analysis aims to make a judgement on the performance and the vulnerability of the company. That’s mean the risks assessment for default and bankruptcy . This analysis generally based on correctives actions in order to improve performance and reduce vulnerability.The objective of this study is to highlight the important role of financial analysis in industrial Algerian companies , in particular National Company of Electronic Industries ENIE sidi bel Abbes , In order to identify the risks of failure that threat it success.